Religious Neutrality, Toleration and Recognition in Moderate Secular States: The Case of Denmark - Laegaard, Sune (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2011)
This paper provides a theoretical discussion with point of departure in the case of Denmark of some of the theoretical issues concerning the relation liberal states may have to religion in general and religious minorities in particular. Liberal political philosophy has long taken for granted that liberal states have to be religiously neutral. The paper asks what a liberal state is with respect to religion and religious minorities if it is not a strictly religiously neutral state with full separation of church and state and of religion and politics. To illuminate this question, the paper investigates a particular case of an arguably reasonably liberal state, namely the Danish state, which is used as a particular illustration of the more general phenomenon of “moderately secular” states, and considers how one might understand its relations to religion. The paper then considers the applicability to this case of three theoretical concepts drawn from liberal political philosophy, namely neutrality, toleration and recognition, while simultaneously using the case to suggest ways in which standard understandings of these concepts may be problematic and have to be refined.